Chemical constituents and antioxidants of Lycium barbarum L. - Alaa Nasser Hussein; Ahlam Hussein Farhoud (University of Thi-Qar Journal of Science, 2021)
The antioxidant activity of the contents of alkaloid and hexane extracts of lycium barbarum was determined and the percentage of free radical inhibition was calculated using DPPH at concentrations (5,10,25,50,75,100) µg/ml using free radical scavenging activity (DPPH) by adding concentrations Various of extracts to DPPH. The inhibitory activity of DPPH free radicals was determined using six different concentrations (5,10,25,50,75,100) µg /ml of lycium barbarum extracts. The results indicated that the concentration of 100 µg /ml showed stronger radical scavenging activity than the lower concentrations. The results of the percentage of free radical inhibition by calculating the IC50 value of the hexane extract of the lycium barbarum plant showed the strongest with a value of (84.5 mcg/ml) compared with the control agent ascorbic acid (4.29 mcg/ml) followed by the alkaloid extract of the bramble plant (5.74 mcg/ml). The total antioxidant capacity of the test samples was calculated using the standard curve as equivalents of ascorbic acid per gram of extracts, for ascorbic acid (y = 0.04245x + 48.177, R² = 0.3224). The results were for lycium barbarum hexane (y = 0.6118x + 46.425, R² = 0.4849) and alkaloid for bramble (y = 0.6337x + 46.361, R² = 0.5284), respectively. The antioxidant activity of the contents of alkaloid and hexane extracts of lycium barbarum was determined and the percentage of free radical inhibition was calculated using DPPH at concentrations (5,10,25,50,75,100) µg/ml using free radical scavenging activity (DPPH) by adding concentrations Various of extracts to DPPH. The inhibitory activity of DPPH free radicals was determined using six different concentrations (5,10,25,50,75,100) µg /ml of lycium barbarum extracts. The results indicated that the concentration of 100 µg /ml showed stronger radical scavenging activity than the lower concentrations. The results of the percentage of free radical inhibition by calculating the IC50 value of the hexane extract of the lycium barbarum plant showed the strongest with a value of (84.5 mcg/ml) compared with the control agent ascorbic acid (4.29 mcg/ml) followed by the alkaloid extract of the bramble plant (5.74 mcg/ml). The total antioxidant capacity of the test samples was calculated using the standard curve as equivalents of ascorbic acid per gram of extracts, for ascorbic acid (y = 0.04245x + 48.177, R² = 0.3224). The results were for lycium barbarum hexane (y = 0.6118x + 46.425, R² = 0.4849) and alkaloid for bramble (y = 0.6337x + 46.361, R² = 0.5284), respectively. The analysis of the diagnosis of the active compounds of the lycium barbarum of the hexane and alkaloid extract using the GC-mass spectrometry technique - also the chemical analysis of the plant showed that the active compounds in the extract of the hexane of the bramble were (22) chemical compounds, and the compound Pentacosane occupied the highest percentages of 17.74%, followed by the compound Nonacos With a percentage of 16.09%, the number of compounds diagnosed in the alkaloid extract of the bramble plant was (14) chemical compounds, and the percentage of Bis (2-ethylhexl) isophthalate was recorded as 58.53%, followed by Pentacosane 8.96% and Tricosane 7.49%, respectively, and others, which appeared in different proportions.